2014
DOI: 10.1111/exd.12531
|View full text |Cite
|
Sign up to set email alerts
|

Role of epidermal γδ T‐cell‐derived interleukin 13 in the skin‐whitening effect of Ginsenoside F1

Abstract: Ginsenoside F1 (GF1) is a metabolite of ginsenoside Rg1. Although GF1 has several benefits for skin physiology, the effect of GF1 on skin pigmentation has not been reported. We found that a cream containing 0.1% GF1 showed a significant whitening effect on artificially tanned human skin after 8 weeks of application. However, GF1 did not inhibit mRNA expression of tyrosinase or dopachrome tautomerase (DCT) in normal human epidermal melanocytes (NHEMs) or cocultured NHEMs/normal human epidermal keratinocytes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Given that ILC2s and NKT cells as well as Th2 cells produce type 2 cytokines such as IL-4 and IL-13, well-known factors of eosinophil and M2 macrophage activation and promotors of WAT browning (Brestoff et al 2014; Han, et al 2014; Lee et al 2015; Lynch et al 2012; Lynch et al 2009), we further investigated whether the macrophage subset differs between brown, epididymal and inguinal fat. The cells in gate R2 (granulocytes) were defined and used for flow cytometry analysis of macrophage and eosinophil subsets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that ILC2s and NKT cells as well as Th2 cells produce type 2 cytokines such as IL-4 and IL-13, well-known factors of eosinophil and M2 macrophage activation and promotors of WAT browning (Brestoff et al 2014; Han, et al 2014; Lee et al 2015; Lynch et al 2012; Lynch et al 2009), we further investigated whether the macrophage subset differs between brown, epididymal and inguinal fat. The cells in gate R2 (granulocytes) were defined and used for flow cytometry analysis of macrophage and eosinophil subsets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies suggested that γδ T cells could induce the secretion of Th2 cytokines, including IL-4, IL-5, and IL-13 [39,40,41]. In a model of pulmonary allergic inflammation, mice that lacked γδ T cells had decreases in IL-5 release as well as in eosinophil and T cell infiltration in contrast to wild-type mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, ginsenoside F1 did not directly inhibit mRNA expression of tyrosinase or DCT in normal human epidermal melanocytes. Instead, ginsenoside F1 enhanced production of IL-13 from human epidermal γδ T cells, and IL-13 significantly reduced the mRNA expression and protein amount of both tyrosinase and DCT resulting in visible brightening of normal human epidermal melanocyte pellets [75] . These results suggest that ginsenosides might be able to regulate melanogenesis via their effect on skin immune cells.…”
Section: Effects Of Ginseng and Its Components On Factors Related To mentioning
confidence: 94%
“…Because the immunostimulatory activities of many ginsenosides are known, it is not surprising that ginsenosides could enhance the reactivity of skin immune cells. In a recent paper, a cream containing 0.1% ginsenoside F1 (a metabolite of ginsenoside Rg1) showed a significant whitening effect on artificially tanned human skin [75] . However, ginsenoside F1 did not directly inhibit mRNA expression of tyrosinase or DCT in normal human epidermal melanocytes.…”
Section: Effects Of Ginseng and Its Components On Factors Related To mentioning
confidence: 99%